Efforts to Foster Religious Maturity Through the Religious Friday Program for Students at SMA Negeri 1 Manyaran - Jundi Syahidan; Amir Mukminin; Ali Mahbub (Yayasan Azhar Amanaa Yogyakarta, 2025)
Religious maturity of students is important in education because it includes the practice of religious values. Therefore, continuous development is needed such as the Religious Friday Program at SMA Negeri 1 Manyaran to increase students' religious awareness and consistency. This study aims to 1). analyze the implementation of the Religious Friday Program, 2). Determine its impact on students' religious maturity, 3). Determine the supporting and inhibiting factors in its implementation at SMA Negeri 1 Manyaran. This research method uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The research subjects included the principal, Islamic religious education teachers or program coordinators, and students of SMA Negeri 1 Manyaran. Research results 1). The implementation of the Religious Friday Program is carried out through three stages, namely planning by the principal and staff, implementation in the form of recitation every Friday morning before learning which begins with reading the Qur'an to instill religious values, and evaluation through routine monthly meetings and monitoring of students' religious habits such as congregational prayer, reading the Qur'an, and praying before and after learning. 2). The Religious Friday program at SMA Negeri 1 Manyaran is effective in increasing students' religious maturity, strengthening their ability to read the Qur'an, understanding the meaning of verses, and increasing Islamic insight. This program also fosters spiritual awareness, making congregational prayer at school and at home a meaningful habit, and has a positive impact on behavior, such as discipline, respect for teachers, cooperation, and mutual assistance, so that religious values ​​are reflected in daily life. 3). Supporting factors for the Religious Friday program include full school support, solid cooperation with the Student Council, and adequate facilities. Meanwhile, the obstacles are that participants are less disciplined, so that activities sometimes run longer than the planned schedule. In addition, there are still participants who use cell phones or talk to themselves during the activity. When the weather is not supportive, especially in the rainy season, activities are hampered because there is no closed space that can accommodate the congregation such as in the school yard.